Thermodynamic properties prediction of the bulk modulus of sediment-hosted disseminated gold deposits (2015)
An equation of state that connects pressure, volume, and temperature are very important in studying the temperature dependence of the thermal bulk modulus. Pressure, and temperature also determines the state of mutter at different depths, different geological environments. A lot of work has been carried out on gold which includes: the determination of the Critical point of gold, geochemistry of gold, the role of organic matter and source of gold in sediment-hosted disseminated gold mineralization using Rock-Eva Analysis. Temperature effects on the universal equation of state of solids among others. Hence, this work aimed at the investigation of high temperature thermodynamic properties prediction of the hulk modulus of sediment-hosted disseminated gold using model with experimental data. Analysis was carried out with pressure vessel, analysis of both pressure and temperature effects on bulk modulus of gold can be use to predict the future state of gold deposits.